Hubungan antara Ketuaan Durian CV Sunan dengan Sifat Fisiknya - Bambang Haryanto; S Royaningsih (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2003)
The objective of this research is to determine relationship between durian maturity of Sunan cultivar and its physical properties. Twelve mature Sunan durians of 100 ± 3 days after fullbloom and 12 immature durians of 70 ± 3 days after fullbloom were used to bedetermined their specific gravity and physical properties. Specific gravity was measured by water displacement and physical properties was visualy identified. After the measurement of specific gravity, all durians were opened (0 measure firmness and total soluble solid (TSS). Durians pulp firmness were measured using Rheometer CD-300 DX (kg unit) while total soluble solid of durians pulp using a digital refractometer Atago PR-201 (% brixs). The result indicated that Sunan durians with oval shape, weight 1,53 1-0,45 kg, diameter 16.0 1-3,0 cm, length 19,0 ±4,0 cm and can be cracked or opened. The specific gravity immature durian was 0,99 ±0,08 gicrn'' and mature durian was 0,89 0,024 g/cm3. The relationship between specific gravity versus firmness of durian pulp, and specific gravity versus total soluble solid are significant as indicated by R2 = 0,89 and R2 = 0,88 respectively. The firmness of immature durian pulp is bigger than 3 kg and the total soluble solid is less than JO % brit